New ischaemic brain lesions in cervical artery dissection stratified to antiplatelets or anticoagulants. (24th February 2015) - Gensicke, H.; Ahlhelm, F.; Jung, S.; von Hessling, A.; Traenka, C.; Goeggel Simonetti, B.; Peters, N.; Bonati, L. H.; Fischer, U.; Broeg‐Morvay, A.; Seiffge, D. J.; Gralla, J.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose To determine the frequency of new ischaemic or hemorrhagic brain lesions on early follow‐up magnetic resonance imaging (MRI) in patients with cervical artery dissection (CAD) and to investigate the relationship with antithrombotic treatment. Methods This prospective observational study included consecutive CAD patients with ischaemic or non‐ischaemic symptoms within the preceding 4 weeks. All patients had baseline brain MRI scans at the time of CAD diagnosis and follow‐up MRI scans within 30 days thereafter. Ischaemic lesions were detected by diffusion‐weighted imaging (DWI), intracerebral bleeds (ICBs) by paramagnetic‐susceptible sequences. Outcome measures were any new DWI lesions or ICBs on follow‐up MRI scans. Kaplan–Meier statistics and calculated odds ratios with 95% confidence intervals were used for lesion occurrence, baseline characteristics and type of antithrombotic treatment (antiplatelet versus anticoagulant). Results Sixty‐eight of 74 (92%) CAD patients were eligible for analysis. Median (interquartile range) time interval between baseline and follow‐up MRI scans was 5 (3–10) days. New DWI lesions occurred in 17 (25%) patients with a cumulative 30‐day incidence of 41.3% (standard error 8.6%). Occurrence of new DWI lesions was associated with stroke or transient ischaemic attack at presentation [7.86 (2.01–30.93)], occlusion of the dissected vessel [4.09 (1.24–13.55)] and presence of DWI lesions on baseline MRI [6.67 (1.70–26.13)]. The type of antithrombotic treatment had no impact either on occurrence of new DWI lesions [1.00 (0.32–3.15)] or on functional 6‐month outcome [1.27 (0.41–3.94)]. No new ICBs were observed. Conclusion New ischaemic brain lesions occurred in a quarter of CAD patients, independently of the type of antithrombotic treatment. MRI findings could potentially serve as surrogate outcomes in pilot treatment trials.